Cytomorphology, clinicopathologic, and cytogenetics correlation of myelomatous effusion of serous cavities: A retrospective review. Issue 9 (19th July 2016) - Harbhajanka, Aparna; Brickman, Arlen; Park, Ji‐Weon; Reddy, Vijaya B; Bitterman, Pincas; Gattuso, Paolo
Abstract : Background: Myelomatous effusions (ME) of the serous cavities are rare. Identification of the atypical plasma cells in the body fluids may be critical for prognostic considerations. Methods: We retrospectively reviewed clinicopathologic findings of 21 serous effusion specimens from 13 cases of ME including 10 pleural, two concurrent pleural and pericardial, and one peritoneal from 1994 to 2014. Result: All 13 patients had bone marrow biopsy‐proven plasma cell myeloma (PCM), including one plasmablastic‐variant, one anaplastic‐variant and one plasma cell leukemia. The time between the bone marrow diagnoses to serous cavity involvement ranged from 43 days to 9 years (mean 2.6 years, median 1.8 years). Monoclonal protein types showed predominant IgA subtypes (50%) including IgA‐kappa (2), IgA‐lambda (3), IgG‐kappa (2), IgG‐lambda (1) free kappa chain (1) and free lambda chain (1) and three unknown. All 13 patients died of disease (median survival 32 days). Concurrent imaging studies showed evidence of adjacent local disease. Cytology of the serous fluids revealed abundant plasma cells with varying degrees of atypia, including large cells with increased N/Cratios, coarse chromatin, and prominent nucleoli. All were CD138 positive. Of these, Cytology confirmed malignancy in 19/21(90%) cases. Five cases were positive for kappa‐light chain and eight cases for lambda‐light chain. Cytogenetics of 3/7 cases showed normal karyotype and 4/7 cases showed complex‐karyotype. The patients with kappa light‐chain had better survival compared to lambda light‐chain ( p = 0.051, log rank test). Conclusion: ME in PCM can present early in the natural history of the disease or very late. The preponderance of IgA‐myeloma and complex‐cytogenetics abnormalities is a noteworthy finding. Although there are different hypotheses regarding how ME develops in PCM, our finding supports the hypothesis that direct spread of PCM into serous cavities is a likely mechanism. Diagn. Cytopathol. 2016;44:742–747. © 2016 Wiley Periodicals, Inc.